Hydrophilic Sponges for Leaf‐Inspired Continuous Pumping of Liquids. Issue 6 (19th April 2017) - Zhou, Tingjiao; Yang, Jinbin; Zhu, Deyong; Zheng, Jieyao; Handschuh‐Wang, Stephan; Zhou, Xiaohu; Zhang, Junmin; Liu, Yizhen; Liu, Zhou; He, Chuanxin; Zhou, Xuechang
Abstract : A bio‐inspired, leaf‐like pumping strategy by mimicking the transpiration process through leaves is developed for autonomous and continuous liquid transport enabled by durable hydrophilic sponges. Without any external power sources, flows are continuously generated ascribed to the combination of capillary wicking and evaporation of water. To validate this method, durable hydrophilic polydimethylsiloxane sponges modified with polyvinyl alcohol via a "dip‐coat‐dry" method have been fabricated, which maintains hydrophilicity more than 2 months. The as‐made sponges are further applied to achieve stable laminar flow patterns, chemical gradients, and "stop‐flow" manipulation of the flow in microfluidic devices. More importantly, the ease‐of‐operation and excellent pumping capacity have also been verified with over 24 h's pumping and quasi‐stable high flow rates up to 15 µL min −1 . The present strategy can be easily integrated to other miniaturized systems requiring pressure‐driven flow and should have potential applications, such as cell culture, micromixing, and continuous flow reaction. Abstract : Durable hydrophilic sponges are fabricated and applied by mimicking the transpiration process through leaves for autonomous and continuous liquid transport. Highly defined flow patterns, chemical gradients, and "stop‐flow" manipulation of the flow are achieved by simply integrating the sponges to microfluidic devices.